The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/catal10101173
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Catalyzed Azidation Reactions

Abstract: A wide range of methodologies for the preparation of organic azides has been reported in the literature for many decades, due to their interest as building blocks for different transformations and their applications in biology as well as in materials science. More recently, with the spread of the use of transition metal-catalyzed reactions, new perspectives have also materialized in azidation processes, especially concerning the azidation of C–H bonds and direct difunctionalization of multiple carbon-carbon bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 152 publications
0
5
0
Order By: Relevance
“…Regarding C–H azidation of anilines, a limited number of literature precedents were available in comparison with aliphatic couterparts (Scheme ). Jiao et al reported a pioneering work on copper-catalyzed C–H azidation employing CuBr and TBHP .…”
mentioning
confidence: 99%
“…Regarding C–H azidation of anilines, a limited number of literature precedents were available in comparison with aliphatic couterparts (Scheme ). Jiao et al reported a pioneering work on copper-catalyzed C–H azidation employing CuBr and TBHP .…”
mentioning
confidence: 99%
“…Mechanistic studies suggest that this reaction involves Mn-catalyzed alkyl radical formation and subsequent azidyl group transfer through Mn III/IV electrocatalysis, which avoids the oxidation to carbocation thus minimizing the side reactions leading to oxygenated products. In addition to these new research articles, we also found a few new review articles that were published during the manuscript review process. …”
Section: Literature Updates: Additions Made During Manuscript Revisionmentioning
confidence: 99%
“…5 However, owing to their inert aromatic C–H bonds the synthesis of aromatic azides is limited in the literature, unlike aliphatic azides. 6–9…”
Section: Introductionmentioning
confidence: 99%
“…5 However, owing to their inert aromatic C-H bonds the synthesis of aromatic azides is limited in the literature, unlike aliphatic azides. [6][7][8][9] Interestingly, it was found that copper can facilitate the synthesis of aromatic azides via C-H functionalization. Aniline, a simple aromatic amine, was converted into its corresponding mono-and di-azides using CuBr (10 mol%) with a yield of 46% and 27%, respectively.…”
Section: Introductionmentioning
confidence: 99%